Efficacy of Online Group Counseling with Mindfulness-Based Cognitive Approach to Enhance Students’ Humility: Array - Rohmatus Naini; Mungin Eddy Wibowo; Mulawarman Mulawarman (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2021)
Character building is an important part of the counseling services in the schools. Humility is a character strengths as a basic development others virtue. This study aims to examine the effectiveness of online group counseling with mindfulness-based cognitive approach to enhance students' humility. This study is pretest posttest control group design with 16 students who divided in to experimental and control groups. To measure the students' humility, authors used 32 items of humility scale (α = .901). Furthermore, to measure mindfulness skills using children and adolescence mindfulness measurement (α = .790). Based on the results of the paired t-test data analysis, obtained the pretest – posttest (t = 18,391; p = .56), posttest – follow up (t = -5,769; p = .001), and pretest – follow up (t = -30.549; p = .001). There was a significant change in the humility score which marked by (p < .05). Comparison analysis between the control group (MD = 12.62; SE = .87; p = .001) was interpreted as a significant increase change in the students' humility. In addition, there is a significant interaction between students' humility in the group as evidenced by (F (2,4) = 56,764, P = .001, Ƞp2 = .73). As the result, there is a significant change in mindfulness group counseling effect on increasing humility and has a large interaction effect.